One-step synthesis of hierarchical SnO2/TiO2 composite hollow microspheres as an efficient scattering layer for dye-sensitized solar cells. (10th February 2019) - Xie, Fengyan; Wang, Jingjing; Li, Yafeng; Dou, Jie; Wei, Mingdeng
Abstract: Hierarchical SnO2 /TiO2 composite hollow microspheres were synthesized via one-step hydrothermal route by using titanium tetrabutoxide as titanium source and potassium stannate and tripolycyanamide as co-additive, and the samples were characterized by XRD, BET, SEM and TEM measurements. The results denoted that the synthesized microspheres with a diameter of ca 500–1000 nm were assembled by thin nanosheets and possessed a large surface area of 199.3 m 2  g −1 . In addition, EDX and element mapping measurements indicated that a small amount of SnO2 nanoparticles uniformly distributed among the nanosheets of microspheres. The hierarchical microspheres simultaneously facilitated dye adsorption, light harvesting, and electron transport, giving rise to a high photovoltaic conversion efficiency of 8.70% when applied as scattering layer for dye-sensitized solar cells, which was a 28.1% improvement compared to that of bare nanocrystalline TiO2 (6.79%, Dyesol) based cell. Graphical abstract: Hierarchical SnO2 /TiO2 composite hollow microspheres with large specific surface area were synthesized and applied as scattering layer for dye-sensitized solar cells, giving a high efficiency of 8.70%, which was a 28.1% improvement compared to that of bare nanocrystalline TiO2 . Image 1 Highlights: Hierarchical SnO2 /TiO2 composite hollow microspheres were synthesized via a one-step hydrothermal route. The nanosheets assembled microspheres exhibited a large specific surface area and superior light scattering capability. Cell with the hierarchical microspheres scattering layer given a high efficiency of 8.70%.